Satu Abad Nahdlatul Ulama dalam sebuah Qasidah Karya KH. Afifuddin Muhajir (Analisis Semiotika Riffaterre) - Mukhammad Lutfi; Abdullah Abdullah; Darsita Suparno (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2023)
The goal of this research is to uncover the true meaning of a Qasidah that employs symbols and indirect expression. The material object studied is Qasidah Nahdliyah Satu Abad Nahdlatul Ulama by KH. Afifuddin Muhajir, also known as Qasidah NSANU, which is a qasidah written to commemorate the centennial of Nahdlatul Ulama (NU) on 16 Rajab 1444 H (7 February 2023 AD) according to the Hijri calendar. The descriptive qualitative method with Riffaterre's semiotic approach was used in this study. Riffaterre provides stages for understanding a poem's full meaning, including heuristic reading, hermeneutic reading, determining models, variants, and matrices, and determining hyprograms. The study's findings indicate that the Qasidah NSANU as a whole contains content about the history of NU's founding, its role in maintaining Indonesian unity, and the figures who played a role in NU's founding. This matrix was discovered after obtaining models in the form of words, phrases, and sentences. It is titled